Distribution of type VI collagen expression in synovial tissue and cultured synoviocytes: relation to fibronectin expression. - Wolf, J (1991)
Type VI collagen has recently been shown to be an important component of connective tissue. Double label immunofluorescence procedures were used to immunolocalize type VI collagen in normal and rheumatoid synovium and its distribution was compared with that of fibronectin. In normal synovium type VI collagen is expressed in the synovial membrane but not in the interstitium of the villus. In rheumatoid synovium, however, type VI collagen is extensively deposited in both the interstitial connective tissue and along the lining of the synovial membrane. Cultured rheumatoid and normal synoviocytes produce type VI collagen and fibronectin and incorporate them into their extracellular matrix. These data suggest that type VI collagen may play a part in matrix remodelling of the inflamed joint.